Pathogenesis Study of Glioma: From Glioma Stem Cells, Genomic Tags, to Rodent Models - Tang, Hailiang (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Despite the past two decades of research progress, glioma still remains the most challenging of all primary central nervous system (CNS) tumors. The complexity of its pathogenesis makes the disease hard to deal with, especially glioblastoma multiforme (GBM, WHO grade IV), the most aggressive brain tumor entity. This Special Issue collect studies that focus on the pathogenesis of glioma, such as its cell origin, the role of GSCs, genomic alterations, animal models, etc. We have collected 10 high-quality papers, and we welcome all researchers to read.